Successive cytotoxicity control by evolutionary surface decorated electronic push-pull green ZnCr-LDH nanostructures: Drug delivery enlargement for targeted breast cancer chemotherapy - Mahsa Kiani; Mojtaba Bagherzadeh; Yousef Fatahi; Hossein Daneshgar; Moein Safarkhani; Ghazal Salehi; Pooyan Makvandi; Mohammad Reza Saeb; Eder C. Lima; Navid Rabiee (OpenNano, 2022)
The reason for the increasing bioavailability and biocompatibility of the porous nanomaterials in the presence of different (bio)molecules is still unknown. The role of difference functional groups and their interactions with the potential bioavailability and biocompatibility is of great importance. To investigate the potential contribution of the electronic effects (especially on the surface of the porous nanomaterials) on their biomedical behavior, a series of surface-decorated green ZnCr-layered double hydroxide (LDH) porous nanocarriers is developed as a non-viral vector. Different conjugations investigated these porous LDHs for optimizing and minimizing the cytotoxicity for targeted breast cancer therapy. Quick low-temperature synthesized ZnCr-LDH nanocarriers method with enlarged drug delivery windows decorated with leaf extracts and benzamide-like molecules revealed a push-pull electronic synergistic effect on cytotoxicity and enhanced cell viability, biocompatibility, aggregations, and interactions with the cell membranes. The pre-defined model drug, doxorubicin (DOX), unraveled chemotherapy performance in response to MCF-7 cell lines, with ≈ 60% drug payload contributed from functional groups of leaf extracts. Moreover, electron-poor and electron-rich benzamide-like molecules attached to the ZnCr-LDH surface enhanced the relative cell viability up to 29% and 32%, respectively. The in vivo experiments on breast cancer of treated mice (H&E) revealed unaggregated cellular arrays and antibacterial activity against E. coli (gram-negative) and S. aureus (gram-positive) bacteria. Benzamide-like ZnCr-LDH nanocarriers showed a suitable zone of inhibition beyond 10 mm, compared to the standard. Cytotoxicity control achieved herein seems promising for the future ahead of nanomedicine.